miR-132 Down-regulates Methyl CpG Binding Protein 2 (MeCP2) During Cognitive Dysfunction Following Chronic Cerebral Hypoperfusion - Yao, Zhao-Hui; Yao, Xiao-li; Zhang, Yong; Zhang, Shao-feng; Hu, Jichang (Current Neurovascular Research, 2017)
Background: Chronic Cerebral Hypoperfusion (CCH) is an important vascular risk factor for vascular-related dementia cognitive impairment and there are no effective measures for the prevention and treatment of cognitive deficit by CCH and the underlying mechanisms are still poorly understood. Methyl cytidine-phosphate-guanosine (CpG) binding protein 2 (MeCP2), regulated by microRNA 132 (miR-132), is as a transcriptional repressor in high concentrations in the brain, which regulates the expression of synaptic proteins and neuroplasticity, and may be involved in the cognitive deficit after CCH. But no relevant studies have been reported. The aim of this study is to investigate the status of MeCP2 expression after CCH and explore whether MeCP2 changes is associated with cognitive deficits after CCH. Methods: We investigated MeCP2 expression after CCH using Western blotting, quantitative Real- Time Polymerase Chain Reaction (qRT-PCR) analysis and immunofluorescence technique in a rat model of permanent bilateral common carotid artery occlusion (2VO) to mimic CCH. We determined the effect of MeCP2 expression on cognitive deficits and neuroplasticity after CCH through lenti-virus stereotaxic injection, the Morris water maze and electrophysiology. Results: CCH contributed to the down-regulation of MeCP2 and mecp2 expressions in the hippocampus and cortex. miR-132 up-regulated by 2VO was distinctly negatively correlated with MeCP2 down-regulation by miR-132 inhibitors. MeCP2 over-expression improved learning and memory impairment, as well as neuroplasticity after 2VO. Brain-Derived Neurotrophic Factor (BDNF) and the activities of its downstream pathways moleculars, tropomyosin receptor kinase B (TrkB) and the cAMP Response Element Binding Protein (CREB) were down-regulated by 2VO and rescued by MeCP2 over-expression. Conclusion: Our study found that miR-132 may participate in the down-regulation of MeCP2 after CCH and MeCP2 down-regulation was possibly involved in the cognitive deficit through regulation of BDNF and its downstream pathways after 2VO. Our findings expounded the underlying mechanisms of cognition deficit after CCH, which contributes to understanding the mechanisms of vascular dementia.
Keywords: miR-132